Video Company Profile LIVE Kota Tangerang Dengan Teknik Editing Menggunakan Adobe Premier Pro - Handayani, Indri; Setiadi, Ade; Ramadani, Rizki (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
The city of Tangerang is a new area resulting from the development of the Tangerang Regency of Banten province. Tangerang City develops and shows itself as a supporting metropolitan city of the capital city of Jakarta. The Tangerang City Government has a large program to build a livable city, worthy of investment, worth a visit, and a smart city that is currently familiar with Tangerang Liveable, Investable, Visitable, E-City (LIVE). The purpose of this study is to introduce the Tangerang City government program. The benefits of this research are as a medium of information and promotion. The method used is by way of field observation and literature study. The problem approach is making analysis, story boards, shooting, video editing and rendering. In the making of this video using Adobe Premier Pro CC 2018 software and the results of the profile program LIVE Kota Tangerang program made in mp4 format then uploaded on youtube social media with the aim of being seen by the wider community, especially the citizens of Tangerang City. Keywords: Tangerang City, LIVE, Video Profile